Capital Expenditure as a Mediator of Regional Financial Independence: Empirical Evidence from East Java - Kurniasih, Evita Dian; Riharjo, Ikhsan Budi; Ardini, Lilis (E-Jurnal Akuntansi; Vol 35 No 2 (2025)DO - 10.24843/EJA.2025.v35.i02.p13, 2025)
This study examines the role of capital expenditure as a mediating variable in the relationship between locally generated revenue (Pendapatan Asli Daerah or PAD), general allocation funds (Dana Perimbangan or DP), economic growth, and the financial independence of district and municipal governments in East Java Province. The analysis utilizes secondary data sourced from the East Java Provincial Budget Realization Report (Laporan Realisasi Anggaran or LRA), obtained from regional budget (APBD) documents, as well as economic growth data published by the Central Statistics Agency for the period 2018–2022. Path analysis is employed to assess the relationships among the variables, while the Sobel test is used to evaluate the mediating effect of capital expenditure. The results indicate that both PAD and economic growth exert a positive influence on capital expenditure and financial independence. In contrast, DP does not have a significant effect on either capital expenditure or financial independence. Furthermore, the Sobel test reveals that capital expenditure does not mediate the relationship between PAD, DP, and financial independence. Keywords: Local Original Income; DP; Economic Growth; Financial Independence; Capital Expenditure.